Methods of the comparative analysis of the insect species composition in different habitats using the software environment R - Sushko, Gennadi G. (Journal of the Belarusian State University. Ecology, 2021)
Analysis of publications on the ecology of communities, in focus insects, over the past five years, available in the international database PubMed Central, showed that the most common scheme for assessing the species composition of different habitats are comparison using multivariate analysis of variance (PERMANOVA) and ANOSIM test, visualization of the differences using ordination (NMDS). The scheme is completed by identifying the species that are most responsible for the differences in the samples, using the IndVal and SIMPER procedures. All these methods can be implemented in the R software environment, which is currently a generally recognized standard in scientific publications in the world. The presented article includes a brief overview of the methods of comparative analysis of the insect species composition. The program code for this implementation in R using the results of our own research is also given.
Keywords: species composition; comparative analysis; insects; community ecology; software environment R